Prevalence and parental perspectives on hand, foot and mouth disease among children in nurseries in Seberang Perai utara district - Zakaria, Nurul Afwani (2021)
Hand, Foot and Mouth Disease (HFMD) is an emerging infectious disease that affects the population worldwide. The objective of this study is to illustrate the trend of HFMD cases registered in Seberang Perai Utara District from 2015 – 2019, to evaluate the relationship between respondents’s knowledge, attitude and practice on HFMD through distribution of questionnaire, to know the relationship between socio demography characteristics with knowledge, attitude and practice on HFMD among parents and finally to compare the level knowledge, attitude and practice towards HFMD among parents in 35 nurseries in this district. The highest number of HFMD cases is in 2018 with 370 cases and the lowest number of cases is in 2017 with 59 cases. Analysis using SPSS Version 22 showed a significant association between age factors with total knowledge score with positive relationship which is r value is 0.343 and p value is 0.004. While relationship factor shows a significant association with total practice score which is r value is 0.297 and p value is 0.013. According to a Chan L.G. (2000), the HFMD virus can survive for a long period out-side the host in suitable conditions, and hence contaminated environments may play important roles in HFMD infection. This implies that asymptomatic infectious individuals and con- taminated environments contribute substantially to new HFMD infections, and so would be targets foreffective control measures. In conclusion, it is vital for intensive intervention in order to enhance knowledge, good practice and awareness on HFMD among the respondents.